O3 type single-crystal high-entropy layered oxide positive electrode material and preparation method thereof
Through co-precipitation method and high-temperature sintering treatment, an O3-type single crystal high-entropy layered oxide cathode material with high electrochemical performance and air stability was prepared, which solved the problem of existing materials' unstable in the air and the capacity reduction under high current density, and achieved excellent cycling performance and air stability.
Patent Information
- Application Number
- CN202510011586.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-04
- Publication Date
- 2025-04-08
Smart Images

Figure CN119776987A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an air-stable O3 type single crystal high entropy layered oxide positive electrode material and a preparation method thereof, as well as application in a sodium ion battery, belonging to the technical field of sodium ion battery materials. Background Art
[0002] With the progress of human society, fossil fuels such as oil, coal and natural gas have become important energy sources for our daily production and life. However, these resources are non-renewable and will release a large amount of greenhouse gases during use, which will have a serious impact on the environment on which we depend for survival, such as global warming and a sharp decline in biological populations. In addition, with the accelerated pace of life, the overexploitation of these resources will further increase the burden on the environment and cause harm to human beings themselves. Therefore, more and more people have begun to pay attention to the development of renewable energy. In recent years, clean renewable energy such as nuclear energy, wind energy, solar energy, tidal energy and hydropower have risen rapidly. However, the production of these energy sources is often intermittent and regional, and is restricted by multiple factors such as time, space, seasons and climate change, and its production and supply are unstable. How to safely and effectively integrate these energy sources into the power grid to meet people's daily energy needs is a key issue that needs to be solved urgently. At present, large-scale energy storage systems are considered to be an effective means to meet this challenge.
[0003] Currently, lithium-ion batteries are widely used in portable electronic devices due to their high energy density, high power density, high operating voltage and good cycle performance. With the popularity of electric vehicles, the demand for lithium resources has risen sharply. However, the reserves of lithium in the earth's crust are relatively scarce and unevenly distributed, resulting in an increase in its production cost year by year, thus limiting its application in the field of large-scale power storage.
[0004] The charge and discharge mechanism of sodium-ion batteries is similar to that of lithium-ion batteries, and the physical and chemical properties of sodium and lithium are also very similar. More importantly, sodium resources are abundant and widely distributed, so the development of sodium-ion battery technology has a positive driving effect on large-scale power storage systems. While reducing costs, sodium-ion batteries also have high specific energy density, excellent energy conversion efficiency, and long charge and discharge cycle life, which has attracted more researchers to study sodium-ion batteries, providing a good opportunity for their commercialization.
[0005] Sodium-ion batteries mainly rely on the movement of sodium ions between the positive and negative electrodes to store and release energy. Due to the abundant sodium resources, low cost, and high safety and stability of sodium-ion batteries, they have become a promising battery technology. The specific capacity of the positive electrode material is much smaller than that of the negative electrode material, which is one of the key factors limiting the development of sodium-ion batteries. Therefore, most research is devoted to the preparation and modification of positive electrode materials. Layered oxide positive electrode materials are a common positive electrode material in sodium-ion batteries. This material is usually composed of transition metals (such as iron, manganese, nickel, cobalt, copper, etc.), oxygen and sodium, and has a layered crystal structure. During the discharge process, sodium ions can be inserted into the oxide lattice from the interlayer, resulting in a redox reaction. During the charging process, sodium ions are deintercalated from the oxide lattice and return to their original state.
[0006] The most common layered oxide cathode materials are P2 and O3 phase structures. In the O3 structure, sodium ions migrate in the sodium layer, that is, from an octahedral position to a nearby octahedral position, and need to pass through the tetrahedral position with face contact, so the diffusion barrier is high and the diffusion coefficient is small. In the P2 phase structure, sodium ions occupy the triangular prism position. There is face contact between each triangular prism, and the diffusion barrier of sodium ions is small and the speed is fast. In terms of electrochemical performance, the rate performance of the P2 phase structure is better than that of the O3 phase structure. In the study of O3 phase materials, the sodium content in the structure is high, and the structure will undergo a series of phase changes such as O3→P3, P3→O′3 during charging and discharging. The structural changes brought about by the phase change will have a certain impact on the cycle performance. In the P2 phase structure, the phase change of P2→O2 can be suppressed by controlling the cut-off voltage, thereby obtaining excellent cycle performance and rate performance. However, because the P2 phase is a sodium-deficient phase structure, its actual reversible capacity (first-cycle charging capacity) is limited, which is not conducive to its use in a full battery. Even though the O3 phase has poor rate performance and low capacity retention due to its structure, the O3 phase structure has sufficient sodium ions and a high reversible specific capacity, making it more suitable for commercial promotion.
[0007] Developing high-capacity and high-reliability O3-type cathode materials is key to advancing the commercialization of sodium-ion batteries. Chemical composition adjustment has been shown to improve the overall structural / chemical stability of the material by stabilizing the crystal structure.
[0008] O3-NaNi 0.5 Mn 0.5 O2 has a high reversible specific capacity, but poor air stability. It is very easy to react with water and carbon dioxide in the air to destroy the structure of the electrode material. Moreover, when the cut-off voltage is higher than 4.0V, the cycle stability is poor and cannot meet practical applications.
[0009] Huang et al. prepared Mg / Ti co-doped NaMn0.45 Ni 0.45 Mg 0.05 Ti 0.05 O2, this material exhibits a high reversible specific capacity of 177.7mAh / g in the voltage range of 2.0-4.2V, and the capacity retention rate has also been improved. After 200 cycles at 0.2C, the capacity retention rate is 72.6%. However, at higher current density, the reversible specific capacity of this material decreases rapidly and the capacity retention rate is poor, so further improvement is needed.
[0010] CN115064657A discloses a high entropy layered metal oxide, which includes Li + , Cu 2+ 、Ni 2+ 、Ni 3+ 、Co 3+ , Fe 3+ 、Al 3+ , Mn 3+ , Mn 4+ 、Ti 4+ Sn 4+ , Sb 5+ At least 5 of the above, the molecular formula of the metal oxide is: Na x Li y Cu z Ni a Co b Fe c Al d Mn e Ti f Sn g Sb k , wherein 0.5≤x≤1, 0≤y, z, a, b, c, d, e, f, g, k≤0.2, and the number of atoms of each metal element accounts for 5-35% of the total number of metal atoms, and the metal oxide is an O3 or P2 phase oxide. When used as a positive electrode material in a sodium ion battery, it can provide a higher specific capacity and energy density, and has excellent cycle stability.
[0011] CN115806319A discloses a NaMn x Fe y Co z Ni a Ti b M cThe layered high-entropy oxide shown in O2. The preparation method of the layered high-entropy oxide includes the following steps: A) Mix the first Na source, Mn source, Fe source, Co source, Ni source, Ti source and M source according to the elemental molar ratio of the layered high-entropy oxide, and ball-mill to obtain a mixture; B) Calcinate the mixture for the first time and then add the second Na source, ball-mill and then calcinate for the second time to obtain the layered high-entropy oxide. The prepared layered high-entropy oxide cathode material for sodium-ion batteries has relatively high air stability, and at the same time has characteristics such as high capacity and high stability.
[0012] CN116314739B discloses a manganese-based layered oxide cathode material. The molecular formula of the manganese-based layered oxide cathode material is Na x Li y M 1-y-z Mn z O2, where 0.5 < x ≤ 1, 0 ≤ y ≤ 0.2, 0.5 ≤ z ≤ 1, and M is at least one of Mg, Zn, Al, Ti, Fe, Co, Ni, Cu. The preparation method of the manganese-based layered oxide cathode material is simple, and the raw materials are widely available. It exhibits a reversible specific capacity of more than 210 mAh / g at a 0.05C rate and a voltage window of 1.5 - 4.6V, has excellent cycling performance, and has excellent air and water stability.
[0013] Through the continuous exploration of researchers, high-entropy layered oxide cathode materials have gradually come into people's view. High-entropy layered oxide cathode materials are composed of five to nine metal ions in solid solution at the TM site, providing excellent electrochemical performance, with high energy density, excellent rate performance and cycling stability. In addition, their improved thermal stability solves the long-standing safety problems in battery technology. These excellent properties stem from high configurational entropy, local disorder and the synergistic effect between various elements, which all contribute to the structural stability during the sodium ion insertion and extraction process. Therefore, it is expected to promote the industrialization of sodium-ion batteries by obtaining high-entropy layered oxide cathode materials with high specific capacity and good cycling stability through a low-cost and high-efficiency preparation process. Summary of the Invention
[0014] Based on the existing high-entropy layered materials, the present invention further improves the process and composition, and prepares an air-stable O3-type single-crystal high-entropy layered oxide cathode material, which has a high initial Coulomb efficiency, high specific capacity, good cycling performance and air stability.
[0015] In one aspect of the present invention, an O3-type single-crystal high-entropy layered oxide cathode material is disclosed, and its chemical general formula is: Na x Mn y1 Ni y2 Co y3 Fey4 Cu y5 M z O2, wherein M is at least one of Ti and Mg, 0.83≤x≤1, 0.2≤y1≤0.45, 0.2≤y2≤0.4, 0.01≤y3≤0.35, 0.2≤y4≤0.4, 0.1≤y5≤0.2, 0.01≤z≤0.15; the unit cell parameter a and the unit cell parameter c of the positive electrode material satisfy a / c≥0.183; the (003) crystal plane diffraction peak intensity I (003) The diffraction peak intensity I (104) Satisfaction: I (003) / I (104) ≥0.76.
[0016] Preferably, the particle size of the positive electrode material does not exceed 20 μm.
[0017] Preferably, the first discharge specific capacity of the positive electrode material at a rate of 0.1C is not less than 127 mAh / g; the first discharge specific capacity at a rate of 1C is not less than 109 mAh / g.
[0018] Preferably, the first coulombic efficiency of the positive electrode material at a rate of 0.1C is not less than 91%; and the capacity retention rate of the positive electrode material after 100 cycles at a rate of 1C is not less than 87%.
[0019] In another aspect of the present invention, a method for preparing an O3-type single crystal high entropy layered oxide positive electrode material is disclosed, comprising the following steps:
[0020] (1) weighing a manganese source, a nickel source, a cobalt source, a copper source and an iron source according to an element molar ratio to prepare a transition metal ion mixed aqueous solution, adding the transition metal ion mixed aqueous solution, a precipitant and a complexing agent to a base liquid under an inert atmosphere to carry out a coprecipitation reaction, and obtaining a hydroxide precursor through aging, washing, filter pressing and drying;
[0021] (2) uniformly mixing the hydroxide precursor obtained in step (1) and the M source, and calcining to obtain an intermediate product;
[0022] (3) uniformly mixing the intermediate product obtained in step (2) with a sodium source to obtain a mixture, and then subjecting the mixture to a first high-temperature sintering to obtain a sintered product;
[0023] (4) adding a sodium supplement to the sintered product obtained in step (3), mixing well and then performing a second high-temperature sintering to obtain an O3-type single crystal high-entropy layered oxide positive electrode material.
[0024] Preferably, the manganese source, nickel source, cobalt source, copper source and iron source in step (1) are one or more of metal oxides, halides, sulfates, nitrates and carboxylates; and the molar ratio of manganese, nickel, cobalt, copper and iron in the mixed aqueous solution of transition metal ions is 0.83-1:0.2-0.45:0.01-0.35:0.2-0.4:0.1-0.2.
[0025] And / or, the volume ratio of the base liquid, the transition metal ion mixed aqueous solution, the precipitant, and the complexing agent in step (1) is 4:0.5-2:1 to 1.5:1-5.
[0026] And / or, the concentration of transition metal ions in the transition metal ion mixed aqueous solution described in step (1) is 2 mol / L to 4 mol / L.
[0027] And / or, the base liquid in step (1) is ammonia water, and the pH value of the base liquid is 9 to 11.5.
[0028] And / or, the concentration of the precipitant in step (1) is 1 mol / L to 6 mol / L, and the precipitant is at least one of sodium hydroxide solution, potassium hydroxide solution, lithium hydroxide solution, and ammonia water; preferably, the concentration of ammonium ions in the complexing agent in step (1) is 0.3 mol / L to 0.9 mol / L, and the complexing agent is ammonia water.
[0029] And / or, the transition metal ion mixed aqueous solution, precipitant and complexing agent in step (1) are added to the base liquid simultaneously by pumping, and the pumping speed is 50mL / h~100mL / h; preferably, the pH value during the coprecipitation reaction in step (1) is 11.0~12.5, the reaction temperature is 45℃~65℃, and the reaction time is 2h~6h; preferably, the coprecipitation reaction in step (1) is carried out under stirring conditions, and the stirring speed is 800rpm~2000rpm.
[0030] And / or, the inert atmosphere in step (1) is argon; preferably, the aging time in step (1) is 6h to 24h; the drying treatment in step (1) is drying at 60°C to 120°C under vacuum conditions for 5h to 24h.
[0031] Preferably, the M source in step (2) is at least one of titanium dioxide, titanium sulfate, titanium hydroxide, magnesium oxide, magnesium carbonate, magnesium hydroxide, magnesium oxalate, magnesium acetate and magnesium nitrate.
[0032] And / or, the mixing in step (2) is performed by at least one of mechanical ball milling and mechanical sand milling, the mixing speed is 300 r / min to 600 r / min, and the mixing time is 2 h to 8 h.
[0033] And / or, the heating rate of the calcination in step (2) is 2°C / min to 15°C / min, the calcination temperature is 700°C to 1200°C, and the calcination time is 4h to 12h.
[0034] Preferably, the sodium source in step (3) is at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium acetate, sodium nitrate, sodium oxalate, sodium citrate and sodium oxide; preferably, the heating rate of the first high-temperature sintering in step (3) is 1 to 10°C / min, the sintering temperature is 700 to 900°C, and the sintering time is 6 to 12h;
[0035] Preferably, the sodium supplement described in step (4) is at least one of Na3N, Na2C2O4, CHNaO2, CH3COONa, and C6H5Na3O7, and the added mass is 0.5% to 5% of the mass of the first high-temperature sintering product.
[0036] And / or, the heating rate of the second high-temperature sintering in step (4) is 1-10°C / min, the sintering temperature is 850°C-1050°C, and the sintering time is 6-24h.
[0037] The third object of the present invention is to provide a sodium ion battery, which is composed of a positive electrode, a separator, an organic electrolyte and a negative electrode; the positive electrode is prepared from an air-stable O3 type single crystal high entropy layered oxide positive electrode material, a conductive additive, a binder and a solvent.
[0038] And / or, the negative electrode is at least one of metallic sodium, hard carbon or antimony-based negative electrode.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] The O3-type single crystal high entropy layered oxide positive electrode material prepared by the present invention can effectively enhance the TM-O bonds in the lattice and improve the stability of the structure, which is helpful to inhibit the irreversible phase change and improve the reversibility of sodium ion deintercalation of the positive electrode material. The prepared positive electrode material has excellent electrochemical properties, namely, high first coulomb efficiency, high specific capacity, high operating voltage, excellent cycle performance and air stability, especially after being placed in the air for a long time, it still shows excellent performance. At the same time, the present invention combines coprecipitation and high-temperature solid phase method to efficiently and quantitatively prepare products, which is of great significance to promoting the practical application and industrialization of sodium ion electronic positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 XRD pattern of the positive electrode material provided in Example 1;
[0042] Figure 2 This is a SEM image of the positive electrode material provided in Example 1;
[0043] Figure 3 The first charge-discharge curve of the positive electrode material provided in Example 1 tested at a current density of 0.1C (1C=120mA / g);
[0044] Figure 4 This is a cycle performance diagram of the positive electrode material provided in Example 3 at a 1C rate;
[0045] Figure 5 This is a cycle performance diagram of the positive electrode material provided in Example 3 at a 5C rate;
[0046] Figure 6 This is a cycle performance diagram of the positive electrode material provided in Example 4 at a 1C rate;
[0047] Figure 7 This is a cycling performance diagram of the positive electrode material provided in Example 6 at a 1C rate. DETAILED DESCRIPTION
[0048] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby. The raw materials and instruments used in the following examples are all commercially available.
[0049] Example 1
[0050] An air-stable O3-type single crystal high-entropy layered oxide positive electrode material, the preparation process of which comprises the following steps.
[0051] S1: Weigh manganese sulfate, nickel sulfate, cobalt sulfate, copper sulfate and ferrous sulfate in molar ratio, dissolve in deionized water, and prepare a 2 mol / L transition metal ion mixed aqueous solution; use ammonia water as raw material to prepare a base liquid with a pH of 11; prepare a 0.3 mol / L ammonia solution as a complexing agent; prepare a 4 mol / L sodium hydroxide solution as a precipitant. Add the base liquid to the sealed reactor, introduce argon to replace the air in the reactor, adjust the solution temperature to 55°C, and the stirring rate to 1500rpm; pump in the complexing agent, transition metal ion mixed aqueous solution and precipitant at the same time, adjust the pH value of the solution in the reactor to 11.5, and after a coprecipitation reaction for 4 hours, age for 12 hours to obtain a precursor slurry. The slurry was filtered and washed 4 times, and dried at 80°C for 24 hours under a vacuum environment to obtain a precursor.
[0052] S2: The precursor, titanium dioxide and magnesium hydroxide were weighed respectively according to the molar ratio of 0.92:0.04:0.04, and mixed evenly by mechanical sand milling. The sand milling speed was 400 rpm and the sand milling time was 4 h. The sand milled mixture was subjected to high-temperature calcination to obtain an intermediate product. The heating rate of the high-temperature calcination was 5°C / min, the calcination temperature was 850°C, and the calcination time was 5 h.
[0053] S3: Weigh the intermediate product obtained in step S2 and sodium carbonate in a molar ratio of 1:0.5, mix them evenly by mechanical ball method, the ball milling speed is 350 rpm, and the ball milling time is 4 hours; put the obtained mixture into a sagger, put it into a muffle furnace, heat it to 850°C at a rate of 5°C / min, keep it warm for 8 hours, and after cooling with the furnace, obtain O3 type high entropy layered oxide.
[0054] S4: The O3 type high entropy layered oxide obtained in step S3 is evenly mixed with the sodium supplement Na2C2O4, wherein the amount of the sodium supplement is 2% of the mass of the oxide; the mixture is loaded into a sagger, placed in a muffle furnace, heated to 900°C at a rate of 5°C / min, kept warm for 12 hours, and cooled with the furnace to obtain an air-stable O3 type single crystal high entropy layered oxide positive electrode material.
[0055] The layered oxide positive electrode material prepared in Example 1 was subjected to XRD test, and the results are as follows: Figure 1 It can be found that all the diffraction peaks of the material are consistent with the O3 type standard card 00-054-0887, indicating that the prepared material is pure phase, has an O3 type crystal structure, belongs to the R-3m space group, has a high diffraction peak intensity, and has good crystallinity.
[0056] The layered oxide positive electrode material prepared in Example 1 was characterized by SEM morphology. Figure 2 As shown, the positive electrode material prepared by the present invention is spherical, some particles are aggregated, and the particle size is less than 20 μm.
[0057] Example 2
[0058] An air-stable O3-type single crystal high entropy layered oxide positive electrode material, the preparation method of which is the same as that of Example 1. The difference is that the O3-type single crystal high entropy layered oxide positive electrode material prepared according to the method of Example 1 is exposed to air for one week, and then the same electrochemical performance test as in Example 1 is performed, and the other steps are the same as in Example 1.
[0059] The results of electrochemical performance tests show that at a current density of 0.1C, the first discharge specific capacity of the positive electrode material is 142.4mAh / g, and the first coulombic efficiency is 98.0%; at a current density of 1C, the reversible specific capacity of the positive electrode material is 130.4mAh / g, and the capacity retention rate after 100 cycles is 89.6%.
[0060] Example 3
[0061] An air-stable O3-type single crystal high-entropy layered oxide positive electrode material, whose preparation method is compared with the preparation method of the O3-type single crystal high-entropy layered oxide positive electrode material in Example 1, except that the diaphragm used in the battery assembly process is a glass fiber diaphragm, and the other steps are the same as in Example 1.
[0062] The method for testing the electrochemical performance is the same as that of Example 1. The first discharge specific capacity of the positive electrode material at a current density of 0.1C is 133.1 mAh / g, and the first coulombic efficiency is 97.4%. Figure 4 As shown in the figure, the reversible specific capacity of the positive electrode material is 115.0 mAh / g at a current density of 1C, and the capacity retention rate after 100 cycles is 90.2%. Under the test conditions of a wide voltage range of 2.0V to 4.5V and a current density of 1C, the positive electrode material exhibits a high reversible specific capacity of 137 mAh / g, and the capacity retention rate after 100 cycles is 87%.
[0063] Figure 5 The cycle curve of the positive electrode material provided in this embodiment under the test conditions of current density of 5C and voltage range of 1.8V to 4.2V. The positive electrode material still shows a high specific capacity and excellent capacity retention rate at high rate, with a reversible specific capacity of 95mAh / g and a capacity retention rate of 97.7% after 100 cycles. It shows that the O3 type single crystal high entropy layered oxide positive electrode material prepared by the high entropy doping strategy of the present invention can be applied to high voltage and high current working environment.
[0064] Example 4
[0065] This embodiment provides an air-stable O3-type single crystal high-entropy layered oxide positive electrode material. The preparation method thereof is compared with the preparation method of the positive electrode material in Example 1, except that the O3-type single crystal high-entropy layered oxide positive electrode material prepared according to the method of Example 1 is exposed to the air for one month, and then subjected to the same electrochemical performance test as in Example 1, and the other steps are the same as in Example 1.
[0066] The electrochemical test results are as follows Figure 6 As shown, under the test conditions of a voltage window of 1.8V to 4.2V and a current density of 0.1C, the first discharge specific capacity of the positive electrode material is 131.9mAh / g, and the first coulombic efficiency is 96.0%; at a current density of 1C, the reversible specific capacity of the positive electrode material is 116.5mAh / g, and the capacity retention rate after 100 cycles is 87.2%, indicating that the O3-type single crystal high-entropy layered oxide positive electrode material prepared by the present invention has excellent air stability.
[0067] Example 5
[0068] An air-stable O3-type single crystal high-entropy layered oxide positive electrode material, the preparation method of which is different from the preparation method of the positive electrode material in Example 1 in that: in step S3, the molar ratio of the intermediate product to sodium hydroxide is 1:0.9, and the other steps are the same as in Example 1.
[0069] The electrochemical performance test process is the same as that of Example 1. Under the test conditions of a voltage window of 1.8V to 4.2V and a current density of 0.1C, the first discharge specific capacity of the positive electrode material provided in this embodiment is 127.2mAh / g, and the first coulombic efficiency is 91.9%; at a current density of 1C, the discharge specific capacity of the positive electrode material is 110.6mAh / g, and the capacity retention rate after 100 cycles is 90.9%.
[0070] Example 6
[0071] An air-stable O3-type single crystal high-entropy layered oxide positive electrode material, the preparation method of which is different from the preparation method of the positive electrode material in Example 1 in that: in step S3, the molar ratio of the intermediate product to sodium hydroxide is 1:0.85, and the other steps are the same as in Example 1.
[0072] The method of electrochemical performance testing is the same as that in Example 1. Figure 7 As shown, under the test condition of current density of 0.1C, the first discharge specific capacity of the positive electrode material provided in this embodiment is 131.4mAh / g, and the first coulombic efficiency is 98.5%; at a current density of 1C, the reversible specific capacity of the positive electrode material is 129.1mAh / g, and the capacity retention rate after 100 cycles is 91.2%.
[0073] Comparative Example 1
[0074] An O3 type high entropy layered oxide positive electrode material, the preparation method of which is different from the preparation method of the positive electrode material in Example 1 in that the preparation method does not include step S5, that is, sodium supplementation and secondary calcination are not performed.
[0075] The method for testing the electrochemical performance is the same as that in Example 1. The O3-type high-entropy layered oxide positive electrode material provided in this comparative example has a first discharge specific capacity of 132.6 mAh / g at a current density of 0.1C, and a first coulombic efficiency of 91.7%. At a current density of 1C, the capacity retention rate of the positive electrode material after 100 cycles is 68.7%.
[0076] Comparative Example 2
[0077] An O3 type high entropy layered oxide positive electrode material, the preparation method of which is different from the preparation method of the positive electrode material in Example 1 in that: no sodium supplement is added in step S5.
[0078] Comparative Example 3
[0079] An O3 type high entropy layered oxide positive electrode material and its preparation and application. The difference between its preparation method and the positive electrode material preparation method in Example 1 is that: the M source is directly mixed with other metal sources for co-precipitation.
[0080] Comparative Example 4
[0081] An O3 type high entropy layered oxide positive electrode material and its preparation and application, wherein the preparation method thereof is different from the positive electrode material preparation method in Example 1 in that: no metal M is added.
[0082] The performance of the positive electrode materials obtained in Examples 1-6 and Comparative Examples 1-4 was tested. O3-type single crystal high entropy layered oxide positive electrode material, PVDF and acetylene black were weighed in a mass ratio of 8:1:1, stirred evenly in N-methylpyrrolidone solution (NMP) to form a slurry, and then coated and dried to obtain a positive electrode sheet. Using a metal sodium sheet as the counter electrode, a 1M NaClO4 / EC:DMC (V / V=1:1) solution as the electrolyte, and a PP film as the diaphragm, a 2032 button cell was assembled in an argon-filled glove box. The performance of the battery was tested using a blue battery tester.
[0083] The results are shown in Table 1.
[0084] Table 1
[0085]
[0086] The preparation method of the O3 type single crystal high entropy layered oxide positive electrode material of the present invention first adopts the co-precipitation method, adds a precipitant into the solution, and precipitates multiple metal ions at the same time, thereby obtaining a spherical precursor with uniform chemical composition, small particle size and uniform distribution; then the precursor, sodium source and M source are evenly mixed, and the first high-temperature sintering is carried out in sequence, and the second high-temperature sintering is carried out after sodium supplementation, so as to obtain the O3 type single crystal high entropy layered oxide positive electrode material, which ensures the high initial efficiency and high specific capacity of the positive electrode material while also having good cycle stability and air stability.
[0087] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. An O3 type single crystal high entropy layered oxide positive electrode material, the general chemical formula of which is: Na x Mn y1 Ni y2 Co y3 Fe y4 Cu y5 M z O2, where M is at least one of Ti and Mg, 0.83≤x≤1, 0.2≤y1≤0.45, 0.2≤y2≤0.4, 0.01≤y3≤0.35, 0.2≤y4≤0.4, 0.1≤y5≤0.2, 0.01≤z≤0.15; the unit cell parameter a and the unit cell parameter c of the positive electrode material satisfy a / c≥0.183; the (003) crystal plane diffraction peak intensity I (003) The diffraction peak intensity I (104) Satisfaction: I (003) / I (104) ≥0.
76.
2. The positive electrode material according to claim 1, characterized in that The particle size of the positive electrode material does not exceed 20 μm.
3. The positive electrode material according to claim 1, characterized in that The first discharge specific capacity of the positive electrode material at a rate of 0.1C is not less than 127 mAh / g; the first discharge specific capacity at a rate of 1C is not less than 109 mAh / g; the first coulombic efficiency of the positive electrode material at a rate of 0.1C is not less than 91%; the capacity retention rate of the positive electrode material after 100 cycles at a rate of 1C is not less than 87%.
4. A method for preparing an O3-type single crystal high entropy layered oxide positive electrode material as claimed in any one of claims 1 to 3, characterized in that: The steps include: (1) weighing a manganese source, a nickel source, a cobalt source, a copper source and an iron source according to an element molar ratio to prepare a transition metal ion mixed aqueous solution, adding the transition metal ion mixed aqueous solution, a precipitant and a complexing agent to a base liquid under an inert atmosphere to carry out a coprecipitation reaction, and obtaining a hydroxide precursor through aging, washing, filter pressing and drying; (2) uniformly mixing the hydroxide precursor obtained in step (1) and the M source, and calcining to obtain an intermediate product; (3) uniformly mixing the intermediate product obtained in step (2) with a sodium source to obtain a mixture, and then subjecting the mixture to a first high-temperature sintering to obtain a sintered product; (4) adding a sodium supplement to the sintered product obtained in step (3), mixing well and then performing a second high-temperature sintering to obtain an O3-type single crystal high-entropy layered oxide positive electrode material.
5. The method according to claim 4, characterized in that The manganese source, nickel source, cobalt source, copper source and iron source described in step (1) are one or more of metal oxides, halides, sulfates, nitrates and carboxylates; the molar ratio of manganese, nickel, cobalt, copper and iron in the mixed aqueous solution of transition metal ions is 0.83-1:0.2-0.45:0.01-0.35:0.2-0.4:0.1-0.
2.
6. The method according to claim 4, characterized in that The volume ratio of the base liquid, the transition metal ion mixed aqueous solution, the precipitant, and the complexing agent described in step (1) is 4:0.5-2:1 to 1.5:1-5; And / or, the concentration of transition metal ions in the transition metal ion mixed aqueous solution described in step (1) is 2 mol / L to 4 mol / L; And / or, the base liquid in step (1) is ammonia water, and the pH value of the base liquid is 9 to 11.5; And / or, the concentration of the precipitant in step (1) is 1 mol / L to 6 mol / L, and the precipitant is at least one of sodium hydroxide solution, potassium hydroxide solution, lithium hydroxide solution, and ammonia water; preferably, the concentration of ammonium ions in the complexing agent in step (1) is 0.3 mol / L to 0.9 mol / L, and the complexing agent is ammonia water; And / or, the transition metal ion mixed aqueous solution, precipitant and complexing agent in step (1) are added to the base liquid by pumping at the same time, and the pumping speed is 50mL / h to 100mL / h; preferably, the pH value during the coprecipitation reaction in step (1) is 11.0 to 12.5, the reaction temperature is 45°C to 65°C, and the reaction time is 2h to 6h; preferably, the coprecipitation reaction in step (1) is carried out under stirring conditions, and the stirring speed is 800rpm to 2000rpm; And / or, the inert atmosphere in step (1) is argon; preferably, the aging time in step (1) is 6h to 24h; the drying treatment in step (1) is drying at 60°C to 120°C under vacuum conditions for 5h to 24h.
7. The method according to claim 4, characterized in that The M source in step (2) is at least one of titanium dioxide, titanium sulfate, titanium hydroxide, magnesium oxide, magnesium carbonate, magnesium hydroxide, magnesium oxalate, magnesium acetate and magnesium nitrate; And / or, the mixing in step (2) is performed by at least one of mechanical ball milling or mechanical sand milling, the mixing speed is 300 r / min to 600 r / min, and the mixing time is 2 h to 8 h; And / or, the heating rate of the calcination in step (2) is 2°C / min to 15°C / min, the calcination temperature is 700°C to 1200°C, and the calcination time is 4h to 12h.
8. The method according to claim 1, characterized in that The sodium source described in step (3) is at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium acetate, sodium nitrate, sodium oxalate, sodium citrate and sodium oxide; preferably, the heating rate of the first high-temperature sintering described in step (3) is 1-10°C / min, the sintering temperature is 700-900°C, and the sintering time is 6-12h; And / or, the sodium supplement described in step (4) is at least one of Na3N, Na2C2O4, CHNaO2, CH3COONa, C6H5Na3O7, and the added mass is 0.5% to 5% of the mass of the first high-temperature sintering product.
9. The method according to claim 1, characterized in that The heating rate of the second high-temperature sintering described in step (4) is 1-10°C / min, the sintering temperature is 850°C-1050°C, and the sintering time is 6-24h.
10. A sodium ion battery, comprising a positive electrode, a separator, an organic electrolyte and a negative electrode; the positive electrode is prepared from the O3 type single crystal high entropy layered oxide positive electrode material according to any one of claims 1 to 3, a conductive additive, a binder and a solvent; Preferably, the negative electrode is at least one of metallic sodium, hard carbon or antimony-based negative electrode.
Citation Information
Patent Citations
Layered high-entropy oxide as well as preparation method and application thereof
CN115806319A
A manganese-based layered oxide positive electrode material and its preparation method and application
CN116314739B
Cited By
High-entropy O3 type layered positive electrode material screening method and device, computer equipment and computer storage medium
CN121306365A